Феноменологія самовизначення особи: базові теоретичні підходи у психології - Лазарук, Андрій (Психологія і суспільство, 2024)
Сутнісний зміст самовизначення людини визначено у проблемному полі чотирьох базових теоретичних підходів: культурно-історичного, аксіопсихологічного, гуманістично-екзистенційного і вчинково-циклічного. Серед основоположних ознак цього феномену виокремлено власну активність особи на шляху до самоздійснення, її компетентність у просторі цінностей і сенсів, індивідуальну спроможність і здатність до творчості й самоперетворення, персональне прагнення до самоактуалізації, свідоме цілепокладання ось-буттєвості, ціннісну зорієнтованість у майбутнє з огляду на теперішнє, повну усвідомленість сенсу свого життя й розуміння власної причетності до світу. Переосмислено концептуальне підґрунтя культурно-історичного підходу до розуміння взаємозв’язків між вітакультурним розвитком соціуму і самовизначенням окремої особи на певному етапі її онтогенезу. Зокрема, самовизначення потрактовано в контексті активного оволодіння суб’єктом соціокультурним досвідом й розглянуто як самодетерміноване змислове психосоціальне утворення, спричинене суспільними правилами і нормативами та особистісно привласнене в ролі його життєдіяльних орієнтирів. Аналіз самовизначення з позицій канонічної психології спричинив обґрунтування його як внутрішнього учинку, який розпочинається у певній ситуації, наснажується просоціальною мотивацією, котра реалізується в розгорнутій у часопросторі дії і завершується процесом рефлексії. Значущим для розуміння сутності вчинкового самовизначення тут аргументовано пізнання, конструювання і створення себе як натхненної особистості. Відрефлексовано здобутки аксіопсихологічного підходу, що дало змогу схарактеризувати самовизначення особистості як результат розвитку її ціннісно-смислової сфери (себто аксіогенезу), траєкторія якої розгортається від усвідомлення мотиву, пов’язаного з цінністю істини, добра, краси, й продовжується під час віднаходження відповіді на головне запитання «для чого?». Здатність до самовизначення проаналізовано у висхідній перспективі, а саме від рівнів індивіда як носія інстинктивної активності та особи як вагомого чинника цілеспрямованої предметної діяльності до ступенів становлення особистості зі сформованою ціннісною свідомістю і розвиненою здатністю морального діяння та до індивідуальності, котра творчо збагачує наявну соціокультурну практику, й аж до найвищого щабля – людини-універсуму. Проаналізовано досягнення гуманістично-екзистенційного підходу, який обстоює реалізацію потреби особи у самоактуалізації, самореалізації і самовизначенні в контексті розгортання сутнісних сил особи, віднаходження й утілення нею сенсу життя як суб’єкта, автора і виконавця свого самісного проєкту, свідомого і відповідального вирішення гносеологічних й онтологічних суперечностей власного існування й самостійного вибору способу вчинкової ось-буттєвості. Головним механізмом самоактуалізації, самореалізації і самоздійснення Я-концепції визначено вчинок самовизначення у єдності його ситуаційного, мотиваційного, діяльнісного і рефлексивного компонентів. Висвітлено самовизначення у форматі вчинково-циклічного підходу, що уможливило пізнання цього феномену як реалізацію суб’єктом власного покликання, що ґрунтується на всеосяжному розумінні значущості й доцільності використання усвідомлених конкретних смислів і персоніфікованих сенсів. Іншим аспектом самовизначення акцентовано зайняття особою активної позиції стосовно вітакультурних цінностей та узмістовлення свого психічного життя. Крім того, розвиток самовизначення розкрито як перехід від когнітивної до емоційно-оцінкової, потім до вчинково-креативної і насамкінець до спонтанно-духовної складових, які розвитково наповнюють внутрішній світ людини суб’єктним, особистісним, індивідуальнісним й універсумним потенціалом. У результаті окреслено етапи вчинкового самовизначення особи – від прагматично-ситуаційного до соціально-мотиваційного і далі до екзистенційно-діяльного й духовно-післядіяльного. Розгортання останніх концептуалізовано як ситуаційну поведінку, соціальну дію, вчинкову реалізацію персональних цінностей і сенсів та рефлексію власної миследіяльності. Отож, у результаті здійсненого теоретичного пошуку обґрунтовано повний учинковий цикл самовизначення людини, який від прагматичних мотивів розгортається в напрямку прийняття й оволодіння соціально значущими вартостями, виявляється у виборі відповідних власній ціннісно-смисловій сфері сенсожиттєвих орієнтирів, реалізується в актах вчинкового самотворення, досягає звершеного ціннісного ідеалу і спілкування із трансцендентним та спричиняє досягнення нею як натхненною особистістю духовного ступеня самовизначення, самоздійснення й самореалізації.The essential content of human self-determination is defined in the problematic field of four basic theoretical approaches: cultural-historical, axio-psychological, humanistic-existential and deed-cyclical. Among the fundamental signs of this phenomenon, it was singled out a person’s own activity on the way to self-realization, their competence in the space of values and meanings, individual capacity and ability for creativity and self-transformation, personal striving for self-actualization, conscious goal-setting of here-existence, valuable orientation to the future with regard to the present, full awareness of the meaning of one’s life and understanding of one’s involvement in the world. The conceptual basis of the cultural-historical approach to understanding the interrelationships between the vita-cultural development of society and the self-determination of a separate person at a certain stage of their ontogenesis has been rethought. In particular, self-determination is interpreted in the context of the subject’s active mastery of ethno-national experience and is considered as a self-determined meaningful psychosocial formation caused by social rules and regulations and personally appropriated as its life guidelines. The analysis of self-determination from the standpoint of canonical psychology caused the justification of it as an internal act that begins in a certain situation, is determined by prosocial motivation, which is realized in an action deployed in time and space and ends with a reflection process. Cognition, constructing and creating oneself as an inspired personality is argued to be significant for understanding the essence of deed self-determination. The achievements of axiopsychological approach are reflected, which made it possible to characterize the self-determination of personality as a result of the development of their value-meaning sphere, that is, axiogenesis, the trajectory of which unfolds from the awareness of the motive associated with the value of truth, goodness, beauty, and continues while finding an answer to the main question «For what?». The ability to self-determination is analyzed in an ascending perspective, namely from the levels of the individual as a bearer of instinctive activity and the person as a significant factor of purposeful objective activity to the stages of the personality’s formation with a formed valuable consciousness and a developed ability for moral action and individuality, which creatively enriches the existing socio-cultural practice and up to the highest level – the human-universum. It has been analyzed the achievement of humanistic-existential approach that argues for the realization of the person’s need for self-actualization, self-realization, and self-determination in the context of the deployment of the essential forces of a person, finding and embodying the meaning of life as a subject, author, and executor of their own project, conscious and responsible resolution of epistemological and ontological contradictions of one’s own existence and independent choice of the method of deed here-existence. The main mechanism of self-actualization, self-realization, and self-fulfillment of Self-concept is determined the act of self-determination in the unity of its situational, motivational, actional, and reflective components. Self-determination in the format of action-cyclical approach is highlighted, which enabled the cognition of this phenomenon as the subject’s realization of their own vocation, which is based on a comprehensive understanding of the significance and expediency of using realized specific meanings and personified senses. Another aspect of self-determination is accented on person taking an active position in relation to vita-cultural values and filling with content the social life. In addition, the development of self-determination is revealed as a transition from cognitive to emotional-evaluative, then to deed-creative and finally to spontaneous-spiritual components, which developmentally fill the inner world of a person with subject, personal, individual and universum potential. As a result, the stages of a person’s deed self-determination are outlined – from pragmatic-situational to social-motivational and then to existential-active and spiritual-post-active. The deployment of the last ones is conceptualized as situational behavior, social action, deed realization of one’s own values and meanings, and reflection of one’s own thinking-activity. Therefore, as a result of the conducted theoretical research, the full deed cycle of human self-determination is substantiated, which unfolds from pragmatic motives in the direction of acceptance and mastery of socially significant values, manifests itself in the choice of relevant reference points in one’s own value-meaning sphere of sense-life, is realized in acts of deed self-creation, and reaches a perfect valuable ideal and communication with the transcendent and causes the achievement by a person the spiritual degree of self-determination, self-fulfillment and self-realization.